PELATIHAN STUDI KELAYAKAN BISNIS USAHA FOTOCOPY HAFIS PROGRAM MBKM MAHASISWA UIGM - Anis Anggreq Ani; Lesi Hertati; Asmawati Asharie (Transpublika Publisher, 2022)
The photocopying business is a small business whose implementation does not require a high level of education, so it can help open up employment opportunities for human resources with low education and will reduce the unemployment rate. will later boost people's purchasing power and in time can contribute to the regional economy. Therefore, this implementation aims to determine the feasibility of the